MENGENAL AJARAN GERAKAN SYI’AH - Mustolehudin Mustolehudin (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2012)
The term Syiah means followers, today conventionally it refers to a moslem group, after the death of the prophet Muhammad SAW, who belive that position of leaders of moslem people is prerogatively holded by Ali and his descendants. The are believed to be sacred. In basic, the practices of Syiah is not much different from other moslem groups (Sunni). Those some manifested differences are in terms of ritual ablution before prayers (wudlu), praying kneeling position (sujud), praying time, temporary marriage (mut`ah), the way folding hand in praying, optional praying in fasting month and one fith tax (khumus).